Local politics as research challenge: the experience of the department for studying political institutions and processes in local practices - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2023)
The article focuses on research efforts of the Department for Studying Political Institutions and Processes of PFRC UB RAS (former Perm Branch for Studying Political Institutions and Processes of Institute of Philosophy and Law of UB RAS) to study local politics in modern Russia. This research covers the last fifteen years; during some part of this period, the topic was outside the Russian political science mainstream, nowadays it is supported and developed by the Russian scientific community. The purpose of the article is to present the subject and problem field of local political research to specialists and everyone interested in local issues and politics in the territorial context.